City Branding through Increasing Tourism: A Case Study of “Serpihan Surga”, Madura, Indonesia - Arie Wahyu Prananta; Agustinus Gergorius Raja Dasion (Migration Letters, 2023)
The model of City Branding in Madura named "Serpihan Surga " and focusing on the strategy of the government to brand their city by a new brand. City Branding revealed that "Serpihan Surga ," which a new brand for Madura, has shown increased tourism in Madura. The government supports the success of the City Branding and people in the Program, Stakeholders, and Culture to boost tourism, which will have an impact on the economic sector and increased tourism significantly. This article using a method of qualitative supported by an interview with some key informants also study of supporting documents. A method of qualitative supported by an interview with six key informants with purposive sampling also study of supporting documents. The NVivo 12 Plus application had been used to analytic the data which Concept Maps, Group Analyze and Cluster Analyze in this research. There are three point of finding in this research are Program based on decree No. 27 of 2017 Art. 7 that Branding "Serpihan Surga " was launched in 2022 and Visit Madura application has function is to help tourists to explore tourism in Madura or called as a tour guide application. Visit Madura application can make it easier for users to find attractions in Madura District by displaying the distance from the user’s location to the destination. Partnership is supported by the infrastructure stakeholders involved, that Team Planalogi, Architecture Team and Expert Team of Economic Development. Of the implementation of the program involved, there is the Government and Society. Cultural, that Cultural preservation in Madura always does every year like the "Festival Wong Mountains" to other annual events. Community involvement in the implementation of City Branding becomes one of the factors.